Exploring the impact of gastric cancer extracellular vesicles glycosylation in cancer communication - Ramos, Cátia Alexandra Coelho (2023)
Tumor cells acquire aberrant glycosylation structures at their surface. One of the most abundant glycosylation modifications present in gastric cancer tissues is the increased expression of truncated O-glycans, such as the sialyl-Tn (STn), which are associated with patients’ poor survival. Interestingly, some of the tumor-associated glycans have already been identified in cancer extracellular vesicles (EVs). Important results from our group have also demonstrated the effect of premature truncation of O-glycans (truncated Oglycans) in modulating the cells aggressive phenotypic behaviour. The general aim of this project was to explore the impact of STn positive EVs in cancer communication, namely in the modulation of the migration capacity of recipient cells. It was hypothesized that the EVs released by cancer cells with more aggressive features could influence the phenotypic behaviour of the recipient cells, namely their migration capacity. In this project, we used the genetically modified gastric cancer cell line, MKN45 SimpleCell (SC), that homogeneously overexpresses the truncated Oglycans Tn and STn, and the wild type version of this model, the MKN45 WT. To achieve this goal, it was first necessary to optimize the best cell culture conditions and the appropriate EV isolation protocol. We study the effects of removing the fetal bovine serum (FBS) from the culture medium for 48h and 72h on cell viability and proliferation rate. In addition, we assessed the impact of using a medium concentration step in the EV isolation protocol. EVs were then characterized by transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA). The presence of a panel of known EV markers, as well as the presence of the truncated O-glycan STn, were evaluated by western blotting. Finally, the role of STn positive EVs on the modulation of the migration capacity of recipient cells was also assessed. Results showed that removing the FBS from the culture medium for 48h or 72h did not affect the viability of both MKN45 WT and SC cells. Therefore, we opted to collect the EVs after growing the cells for 72h in medium without FBS. In addition, a better EV yield was achieved when isolating the EVs without the medium concentration step when compared to the protocol with this additional step. TEM images showed the presence and integrity of the EVs isolated from both MKN45 WT and SC cell lines. In addition, western blotting results showed the presence of the specific EV markers HSP70, synthenin-1, actin, Alix, CD9 and CD81 in MKN45 WT and SC derived EVs. Curiously, an enrichment of STn antigen was found in SC EVs when compared to the parental cells. NTA results revealed that MKN45 SC cells secreted more EVs than the MKN45 WT cell line. Additionally, an increased migration capacity of the MKN45 SC cell line was observed when comparing with the MKN45 WT cell line. Interestingly, when coculturing the MKN45 WT cells with STn positive EVs an increase in the migration capacity of these cells was observed when compared with the untreated cells. This project was important to demonstrate that STn positive EVs, secreted from cells with high expression of this truncated O-glycan, could effectively modulate the migration capacity of recipient cells. In the future, it will be interesting to explore the impact of STn positive EVs on tumor growth, invasion and metastasis. It will be important to find which mechanisms are regulating the acquired aggressive phenotype caused by STn positive EVs. These results would be crucial for the better understanding of the impact of EV glycosylation, namely the truncated O-glycans, in cancer communication and may bring numerous benefits to the clinical outcome of gastric cancer patients.